An Individual Tree Growth Model for Juvenile Cork Oak Stands in Southern Portugal - Paulo,Joana A. (2009)
The juvenile and adult stages in cork oak are distinct because of the periodic debarking of the stem and branches that characterizes the adult stage. This fact implies the use of diameter under bark for the adult stage while diameter over bark is the natural variable for juvenile stands in growth and yield studies. Tree growth in the adult stage may also be affected by the periodic debarking. The differences between the two stages justify the development of different models for each of them. The objective of this paper is to develop an individual tree growth and yield model for juvenile cork oak stands for general application on the cork oak distribution area in Southern Portugal. The most important modules of this growth model were developed using data collected from a large number of trees in the juvenile stage, from several plots distributed around the South of Portugal. These modules were: an individual tree diameter growth model, a height-diameter model and a model for crown diameter prediction.